Risk of acute arterial and venous thromboembolic events in eosinophilic granulomatosis with polyangiitis (Churg–Strauss syndrome). Issue 5 (6th May 2021) - Bettiol, Alessandra; Sinico, Renato Alberto; Schiavon, Franco; Monti, Sara; Bozzolo, Enrica Paola; Franceschini, Franco; Govoni, Marcello; Lunardi, Claudio; Guida, Giuseppe; Lopalco, Giuseppe; Paolazzi, Giuseppe; Vacca, Angelo; et al.
Eosinophilic granulomatosis with polyangiitis (EGPA; formerly Churg–Strauss syndrome) is a rare anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) characterised by respiratory manifestations and systemic organ involvement [1]. Particularly, cardiac manifestations occur in 40–60% of patients, representing the leading cause of mortality [2]. Recent reports suggest that venous thromboembolic events might also represent a consistent burden of disease [3, 4], as already known for the other AAVs [5–7], possibly due to eosinophil-mediated vascular inflammation [5]. Nevertheless, the occurrence of arterial and venous thrombotic events (AVTEs) has never been systematically explored in EGPA. Eosinophilic granulomatosis with polyangiitis is associated with a high risk of acute arterial and venous thromboembolic events (AVTE), particularly around the time of diagnosis and in patients with high disease activity or history of previous AVTE http://bit.ly/3sKnvzQ